Enhancing Learning Engagement in Madrasah Ibtidaiyah Students Through AR-Based Monopoly Media in History Education - Anis Muzkiyah; Dicky Anggriawan Nugroho (AL-ISHLAH: Jurnal Pendidikan, 2024)
Communication activities that occur between teachers and students in a class should provide positive feedback. However, sometimes a problem arises that makes communication activities ineffective. The lack of learning media innovation from teachers causes students to have a low interest in learning. This research aims to develop augmented reality-based monopoly game learning media as a breakthrough in increasing student learning interest. The research and development method used in this research is the ADDIE development model. The learning media used has been validated by media experts with a score of 85% and is on the criteria of being very feasible. In addition, the results of evaluation questionnaires from teachers who showed 96% lift and assessment results from students who showed scores of 38 out of a total of 40 scores on student evaluation questionnaires proved that learning media increased students' interest in learning. Through the development of learning media in this study, researchers hope that educators can be more innovative and creative in creating fun learning so that students also become more enthusiastic about teaching and learning activities in the classroom.